A COMPARATIVE ANALYSIS OF ZAKAT AND WAQF MANAGEMENT IN INDONESIA AND PAKISTAN - Marenza, Silvya Eka (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This research aims to compare the management of zakat and wakaf in Indonesia and Pakistan, focusing on institutional aspects, regulations, effectiveness, and transparency. The method involves a comparative analysis between the two countries, collecting data from various primary and secondary sources as well as interviews with experts. The results show significant differences in the approach to zakat and wakaf management between the two countries, with Indonesia tending to be more advanced in terms of institutions and regulations, while Pakistan faces challenges related to effectiveness and transparency. Research recommendations highlight the need for cross-country experience exchange, increased transparency, and regulatory updates to enhance the effectiveness of zakat and wakaf management. The implications of this research include an increased understanding of factors influencing zakat and wakaf management and the potential to enhance the socio-economic benefits of these resources in both countries.